Cryoprecipitate as an alternative to platelet transfusion in thrombocytopenia. Issue 1 (8th December 2021) - Crispin, Philip; Hicks, Sarah; Coupland, Lucy A.; Ali, Sidra; Gardiner, Elizabeth E.
Abstract: Platelet transfusions are not always available for bleeding in severe thrombocytopenia, as storage outside of major centers is limited by their short shelf‐life. Data are lacking to support alternative available blood products; however, additional fibrinogen has been shown to enhance clot formation in vitro. To test the hypothesis that cryoprecipitate supplementation could improve clot formation in severe thrombocytopenia, eight hematological malignancy patients with platelet counts under 10 × 10 9 /L each had 10 units of apheresis cryoprecipitate transfused prior to planned prophylactic platelet transfusions. The primary endpoint of thromboelastometry amplitude at 20 min increased by a mean of 5.1 mm ( p  < 0.01) following cryoprecipitate transfusion despite persisting thrombocytopenia. Thromboelastometry clotting times reduced by a mean of 7.8 s ( p  < 0.05) and alpha angle increased by a mean of 10.6⁰ ( p  < 0.01). These results are consistent with cryoprecipitate enhancing the strength of the fibrin/platelet meshwork within the forming thrombus. While platelet transfusion remains the standard of care, where platelet supplies are limited, these data provide a rationale for the use of cryoprecipitate to obtain hemostasis in bleeding thrombocytopenic patients.